Organisation of extracellular matrix proteins laminin and agrin in pericapillary basal laminae in mouse brain - Hoddevik, Eystein Hellstrøm (Brain Struct Funct, 2020)
Evidence suggests that extracellular matrix molecules of perivascular basal laminae help orchestrate the molecular assemblies at the gliovascular interface. Specifically, laminin and agrin are thought to tether the dystrophin-associated protein (DAP) complex to the astrocytic basal lamina. This complex includes α-syntrophin (α-Syn), which is believed to anchor aquaporin-4 (AQP4) to astrocytic endfoot membrane domains. We have previously shown that the size of the perivascular AQP4 pool differs considerably between brain regions in an α-Syn-dependent manner. Also, both AQP4 and α-Syn occur at higher densities in endfoot membrane domains facing pericytes than in endfoot membrane domains facing endothelial cells. The heterogeneous distribution of AQP4 at the regional and capillary level has been attributed to a direct interaction between AQP4 and α-Syn. This would be challenged (1) if the microdistributions of laminin and agrin fail to align with those of DAP and AQP4 and (2) if targeted deletion of α-Syn leads to a loss of laminin and/or agrin. Here, we provide the first detailed and quantitative analysis of laminin and agrin in brain basal laminae of mice. We show that the microdistributions of these molecules vary in a fashion that is well aligned with the previously reported microdistribution of AQP4. We also demonstrate that the expression patterns of laminin and agrin are insensitive to targeted deletion of α-Syn, suggesting that α-Syn deletion affects AQP4 directly and not indirectly via laminin or agrin. These data fill remaining voids in the current model of how key molecules are assembled and tethered at the gliovascular interface. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00429-020-02036-3) contains supplementary material, which is available to authorized users.